Determinants of Paddy Field Conversion in Java 1995-2013 - Febrina, Wina Dwi (Research and Development Agency Ministry of Home Affairs, 2017)
Java is the biggest rice supplier with the largest paddy field compared to other islands in Indonesia. On the other side, economic growth needs more and more land for infrastructure growth. It was suggested that the growth would convert paddy field in Java to non-agriculture use. This paper reports the growth of land conversion, especially from paddy field to other utilization, in Java Island using panel data (provincial data 1995-2013). The data then treated as the dependent variable in the regression analysis for determining the factors that are significantly influential. The relative strengths of the influential factors are then compared using the concept of elasticity. It is found that farmers term of trade and GDP of manufacturing industries sectors significantly influence the land conversion. Meanwhile, the size of the population and the size of medium and large companies of manufacturing industries do not significantly influence the land conversion.